Memahami Dimensi dan Dampak Kualitas Makanan terhadap Kesehatan Masyarakat: Literature Review - Riyan Ningsih; Eka Putri Rahayu (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Food quality is a very important aspect of public health.The WHO estimates that 600 million cases of food poisoning, or nearly 1 in 10 people in the world, fall ill after eating contaminated food, resulting in 420,000 deaths each year. Furthermore, the mortality rate from accidental poisoning per 100,000 Indonesians is 0.3. Food quality plays a crucial role in influencing the quality of life of the Indonesian people. Moreover, the mortality rate due to accidental poisoning per 100,000 Indonesian residents is 0.3. Food quality plays a crucial role in influencing consumer satisfaction and public health.  The purpose of this study is to explore the dimensions and impacts of food quality on public health.  In this literature, we examine various aspects of food quality, including physical and organoleptic dimensions, microbiological aspects, hygiene, and sanitation. Through a review of several studies, we conclude that food quality is a multidimensional construct encompassing physical, organoleptic, microbiological, and hygiene and sanitation aspects. A comprehensive approach is needed covering: improvement of sanitation infrastructure, training and certification of food handlers, strengthening of monitoring and evaluation systems, enforcement of regulations, and further research to measure the effectiveness and impact of interventions.